Pengaruh Budaya Organisasi Terhadap Senjangan Anggaran dengan Komitmen Organisasi dan Partisipasi Anggaran Sebagai Variabel Intervening - Aisyah, Nur; Susilowati, Endah (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2021)
Abstract The purpose of this study is to determine the effect of organization culture on budgetary slack with organizational commitment and budget participation as mediating variables. This research method uses a quantitative approach. The data collection technique is a questionnarie. The sample in this study uses purposive sampling that is 60 samples. The analysing technique of this study uses Smart PLS 3.0. The results of this study are organization culture that has a significant effect on organization commitment, organization culture has a significant effect on budgetary participation, organization commitment has a significant effect on budgetary slack, organization culture doesn't have a significant effect on budgetary slack, organization culture has an effect on budgetary slack mediated by organization commitment, and organization culture influence the budgetary slack which is mediated by budget participation.